An exploration of punctuation in digital discourse - Albritton, M. Andrew (2015)
In this thesis, some of the functions of punctuation marks in digital discourse are explored. A theoretical model of punctuation mark function was generated specifically for this project and is based in rhetorical theory. According to this model, punctuation marks can function in three ways: First, they can build or damage the credibility of the writer; second, they can clarify the meanings of texts in a number of ways; and third, they can convey emotional and relational meaning. Two empirical studies are presented in this thesis. The first uses data from text-messages and the second uses data from message boards. For the text-message study, a new method of data collection was employed: Respondents were given Discourse Completion Tasks that asked what text-message they would send in a series of four respective hypothetical contexts; they were then asked to type out and send their responses, in text-messages, to email addresses. For the second study, data was taken from Reddit message boards on the Internet. In the analysis sections of the thesis, punctuation marks are examined in the collected data according to the rhetorical model with special attention being paid to how punctuation marks can convey emotional and relational meaning; and they are also examined according to how they influence speech acts. It is concluded that different punctuation marks can function in a variety of ways, and that punctuation marks can exert a powerful influence on speech acts. It is furthermore concluded that the thesis’s rhetorical model is effective both as a description of the ways punctuation marks can function and as a guide for analysis.